Effects of Henna-Violet Based Topical Preparation in Preventing and Reducing the Severity of Radiation-Induced Dermatitis in Breast Cancer Patients: A Randomized, Double-Blind Clinical Trial - Kamian , Shaghayegh; Heydarirad, Ghazaleh; MehrArdestani, Mozhgan; Lesan, Mansour (Novelty in Biomedicine, 2022)
Background: Radiation-induced dermatitis (RID) is a common side effect of radiotherapy. The present work attempts to examine the effect of using henna- violet based topical preparation to prevent and decrease the severity of RID in patients with breast cancer. Materials and Methods: The study was carried out as a prospective, double-blind clinical study on 43 breast cancer patients aged 18-75 years. The subjects had undergone breast-conserving surgery, and radiotherapy was scheduled for them. The participants were categorized randomly into two groups; patients who received the henna- violet based topical preparation and patients who received a placebo twice a day for six weeks. The level of the RID score was measured every week based on the toxicity criteria of the radiation therapy oncology group (RTOG). Results: The henna- violet based topical preparation decreased the severity of RID and delayed the development of grade 2 RID for two weeks. In addition, the initiation of grade 3 RID was deferred for one week. There was a significant decrease in grade 2 RID (20% vs. 56.52%) as well as grade 3 RID (10% vs. 26.09%) in the patients who received the henna- violet based topical preparation at the end of the 6th week (P=0.004). Conclusion: This cream, which contained henna and violet, had no severe adverse effects, could prevent RID and decreased the grade of dermatitis in breast cancer patients compared to the placebo.